Chitosan-Based Nanoparticles for Targeted Nasal Galantamine Delivery as a Promising Tool in Alzheimer's Disease Therapy - Dilyana Georgieva; Denitsa Nikolova; Elena Vassileva; Bistra Kostova (MDPI AG, 2023)
Natural alkaloid galantamine is widely used for the treatment of mild to moderate Alzheimer's dementia. Galantamine hydrobromide (GH) is available as fast-release tablets, extended-release capsules, and oral solutions. However, its oral delivery can cause some unwanted side effects, such as gastrointestinal disturbances, nausea, and vomiting. Intranasal administration is one possible way to avoid such unwanted effects. In this work, chitosan-based nanoparticles (NPs) were studied as potential GH delivery vehicles for nasal application. The NPs were synthesized via ionic gelation and studied using dynamic light scattering (DLS) as well as by spectroscopic and thermal methods. The GH-loaded chitosan-alginate complex particles were also prepared as a way to modify the release of GH. The high loading efficiency of the GH was confirmed for both types of particles, at 67% for the GH-loaded chitosan NPs and 70% for the complex chitosan/alginate GH-loaded particles. The mean particle size of the GH-loaded chitosan NPs was about 240 nm, while the sodium alginate coated chitosan particles loaded with GH were expectedly bigger, with a mean particle size of ~286 nm. GH release profiles in PBS at 37 °C were obtained for both types of NPs, and it was found that the GH-loaded chitosan NPs allowed the prolonged release of the incorporated drug for a period of 8 h, while the complex GH-loaded chitosan/alginate NPs released the incorporated GH faster. The stability of the prepared GH-loaded NPs was also demonstrated after 1 year of storage at 5 °C ± 3 °C.